The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.24934/eef.v20i30.1758
|View full text |Cite
|
Sign up to set email alerts
|

O direito a uma educação comprometida com a Educação das Relações Étnico-Raciais / The right to an education committed to the Education of Racial-Ethnic Relations

Abstract: ResumoEste artigo trata da Educação das Relações Étnico-Raciais (ERER) como um direito da educação, sobretudo da educação infantil. O Estado é o principal responsável por assegurar uma educação de qualidade, emancipatória, afinal, ele não pode adotar uma postura neutra em relação à ERER. Torna-se relevante discutir sobre as ações discriminatórias para se detectar em que medida elas influenciam e aparecem no cotidiano educacional. A ERER está garantida a todos os níveis de educação por meio de legislações como:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…This representation, often unintentional and rarely addressed in teacher training, highlights the influence of whiteness on the conception of these environments. Silva (2021) analyzed 13 academic works on school relations in Early Childhood Education. The results indicated that racial equality is still an objective to be achieved, and that whiteness and racism permeate relationships in the school environment, whether in pedagogical practices or in the imagination of students and teachers, even if indirectly.…”
Section: Resultsmentioning
confidence: 99%
“…This representation, often unintentional and rarely addressed in teacher training, highlights the influence of whiteness on the conception of these environments. Silva (2021) analyzed 13 academic works on school relations in Early Childhood Education. The results indicated that racial equality is still an objective to be achieved, and that whiteness and racism permeate relationships in the school environment, whether in pedagogical practices or in the imagination of students and teachers, even if indirectly.…”
Section: Resultsmentioning
confidence: 99%